Building trust : developing the Russian financial sector. - Fuchs, Michael J. (Michael Joseph), 1951-; World Bank. (Washington, DC : World Bank, 2002)
This book addresses challenges for the financial sector in Russia, the problems and potential solutions that it identifies will be of relevance to individuals and organisations charged with containment of banking risks, improvement of financial intermediation, and the fostering of trust in banking institutions---especially within other transition economies.
"This book was produced by a World Bank team led by Michael Fuchs who planned, coordinated, and edited the book."
Includes bibliographical references.
gau 19/06/14
Loans
Keywords: Banks and banking -- Russia (Federation); Finance -- Russia (Federation)